LOCAL DEVELOPMENT INITIATIVES AS PROMOTERS OF SOCIAL INNOVATION: EVIDENCE FROM TWO EUROPEAN RURAL REGIONS - Novikova, Marina; Ferreiro, Maria de Fátima; Stryjakiewicz, Tadeusz (Quaestiones Geographicae, 2020)
Social innovation entered the academic discourse several decades ago and has since been seen as a way of tackling existing problems in various contexts. Although an extensive body of research has been conducted into the role of social innovation in urban context, there is still a gap when it comes to studying the role of social innovation in the development of rural areas. In this paper, an attempt is made to look at the role of Local Action Groups (LAGs) and Local Development Associations (LDAs) as promoters of social innovation in rural areas in Austria and Portugal, aiming to understand the role of such organisations and the challenges faced by the latter in promoting social innovation.